Impact positif des activités de bénévolat pour les jeunes bénévoles de l’Association Citrus, France - Zumroh Rofii’ Ati; Mohamad Syaefudin (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
Objectives: 1. To describe some of the volunteer activities carried out by volunteers at the Citrus Laguépie Association, France. 2. Describe the benefits of volunteering to improve the personal abilities of volunteers at the Citrus Association, Laguépie, France. Design and methods: the design of this research is descriptive qualitative. The data collection method was carried out through online interviews with six young volunteers who had completed volunteering at the Citrus Association in France between 2019 and 2020. Results: From the data obtained, it was found that volunteering activities in the Citrus Association in the form of cultural exchange activities, popular education, and social service. Volunteers stated that they had a long-term positive impact on themselves, starting with self-confidence and becoming a more open person.